1995
DOI: 10.1177/002076409504100404
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the General Health Questionnaire (GHQ-30) in Japanese Middle-Aged and Elderly Residents

Abstract: We conducted Goldberg's 30-item General Health Questionnaire (GHQ) on 1,216 Japanese general population aged 40-92. Among them, 9.8% of males and 13.7% of females scored over the cut-off point which is used to indicate minor psychiatric disorders. Factor analysis was carried out using the Likert method and eight factors labelled as follows were selected: depression, anxiety and tension, anergia, interpersonal dysfunction, difficulty in coping, insomnia, anhedonia and social avoidance. The mean value of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
2
17
1
2
Order By: Relevance
“…Ohta et al 17,18) reported a prevalence rate of 13.7-17.4% in the general female population, and Shigemi et al 19,20) with these previous reports, the prevalence of high GHQ-30 scores in the female doctors in this study (41.6%) was high. Researchers in the UK have shown that psychological distress levels among doctors are higher than that of the general population 3,22) .…”
Section: Discussionsupporting
confidence: 78%
“…Ohta et al 17,18) reported a prevalence rate of 13.7-17.4% in the general female population, and Shigemi et al 19,20) with these previous reports, the prevalence of high GHQ-30 scores in the female doctors in this study (41.6%) was high. Researchers in the UK have shown that psychological distress levels among doctors are higher than that of the general population 3,22) .…”
Section: Discussionsupporting
confidence: 78%
“…However, our results in independent-living elderly women showed significant positive correlations between age and severe depression and social dysfunction. Jorm reported that aging is associated with an intrinsic reduction in susceptibility to anxiety and depression (33), and Ohta observed that depression increased with age although marked changes were not found in the GHQ scores (34). However, we found a positive correlation between age and depression scores in the GHQ sub-scale, although no correlation was found between age and anxiety/insomnia scores.…”
Section: Discussioncontrasting
confidence: 68%
“…As no study has assessed the emotional disturbance among Japanese graduate students nor among age matched young adults, in order to place the observed rate within the Japanese context we compared our findings to previously reported prevalence rates of other sub-populations in Japan using the same method. In a community sample of the middle-aged and elderly 12.3% suffered from Pallos,Yamada,and Okawa 9 JOURNAL OF COLLEGE STUDENT PSYCHOTHERAPY emotional disturbance (Ohta et al, 1995), meanwhile among employees in an electric company 37.8% (Shigemi et al, 1997). The highest prevalence rate was reported among evacuees of a volcanic eruption (Ohta et al, 2003), of them 45.6% of respondents were still suffering from emotional disturbance 44 months after the eruption.…”
Section: Discussionmentioning
confidence: 95%
“…The resulting factor structure was interpreted and factors labeled. Labels of the extracted factors were based on recommendations from the original authors (Goldberg & Williams, 1991) in line with existing factor analytic studies of GHQ-30 in Japan (Iwata et al, 1994;Ohta et al, 2003;Ohta et al, 1995;Takeuchi & Kitamura, 1991). The analysis was carried out on the raw data of Likert scores to avoid the loss of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation